2018
DOI: 10.1111/jam.14059
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota lipid metabolism varies across rainbow trout (Oncorhynchus mykiss ) phylogeographic divide

Abstract: The possibility of genetic variation controlling intestinal microbiome diversity could have significant impacts on strain selection for rainbow trout aquaculture, especially given the consistent rearing conditions experienced in our sample populations likely result in differences in intramyocellular lipid storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids ( Liu et al, 2016 ; Dehler, Secombes & Martin, 2017 ; Lyons et al, 2017 ; Wei et al, 2018 ; Yildirimer & Brown, 2018 ). Actinobacteria, such as Corynebacterium and Gordonia ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids ( Liu et al, 2016 ; Dehler, Secombes & Martin, 2017 ; Lyons et al, 2017 ; Wei et al, 2018 ; Yildirimer & Brown, 2018 ). Actinobacteria, such as Corynebacterium and Gordonia ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found that the metabolism contributes the most to the predictive pathways of the salmonid gut microbiome, followed by information and cellular processing (Dehler et al, 2017;Lyons et al, 2017c;Yildirimer and Brown, 2018). Specifically, our results agree that a high proportion of pathways are attributed to amino acid, carbohydrate, and energy metabolism and to a lesser extent vitamin and lipid metabolism (Dehler et al, 2017;Lyons et al, 2017c).…”
supporting
confidence: 89%
“…Very few studies exist that compare the impact of the gut microbiome on lipid metabolism in fish, despite a connection between n-3/n-6 fatty acids and gut microbes. A study by Yildirimer and Brown (2018) found that a population of wild rainbow trout had lower lipid absorption and higher activation of lipid metabolism pathways, specifically linoleic acid (18:2n-6). Wild fine flounder (Paralichthys adspersus) were found to have higher activation of fatty acid metabolism and biosynthesis of unsaturated fatty acids pathways compared to farmed flounder presumably fed a formulated diet higher in lipid and LC-PUFA (Ramírez and Romero, 2017).…”
mentioning
confidence: 99%
“…In regards to metabolic pathways, the predictive functions of gut microbes in the present studies agree with previous findings that they are mainly associated with the metabolism of carbohydrates, amino acids, energy and to a lesser extent lipids (Liu et al, 2016;Dehler, Secombes & Martin, 2017;Lyons et al, 2017;Wei et al, 2018;Yildirimer & Brown, 2018). Actinobacteria, such as Corynebacterium and Gordonia (Fig.…”
Section: Discussionsupporting
confidence: 92%